UTILIZAÇÃO DA FARINHA DE BABAÇU COMO EXTENSOR ALTERNATIVO NA PRODUÇÃO DE PAINÉIS COMPENSADOS - Érika da Silva Ferreira; Edvá Oliveira Brito; Setsuo Iwakiri; Silviana Rosso; Djeison Cesar Batista (Ciência Florestal, 2009)
This work aims at evaluating the potentiality of babaçu flour under differents percents (0%, 50%, 75%, and 100%) as alternative extensers to wheatmeal for plywood manufacturing. Third three panels with five veneers were produced using Araucaria angustifolia (Bert.) Ktze, with urea-formaldehyde - UF and phenol-formaldehyde - FF resins and being three panels per treatment. The following formulations (in parts per wheight) were used: UF resin - 100 x extender - 50 x water - 50 x catalyst - 7 and FF resin - 100 x extender - 18 x water - 22. The results of both glue line shear strength obtained for plywood manufactured with urea-formaldehyde and phenol-formaldehyde resins showed the feasibility of the use of babaçu flour as the extender in parcial or total substitution of wheat flour in the plywood manufactures.